Novel Solutions or Rebranded Approaches: Evaluating the Use of Nature-Based Solutions (NBS) in Europe - O'Sullivan, Fearghus; Mell, Ian; Clement, Sarah (Frontiers in Sustainable Cities, 2020)
The Nature-Based Solutions (NBS) concept is the most recent entry to discussions around how ‘nature’ can be mobilised to render urban areas more resilient to the threat of climate change. The concept has been championed by the European Commission (EC) as a tool that can transform contemporary environmental, social and economic challenges into opportunities for innovation, bolstering Europe’s position as a leader in climate change mitigation and adaptation. With its current research and innovation programme – Horizon 2020 – the EC looks to position itself as the global NBS frontrunner, providing funding to cities to act as NBS demonstrator projects across the continent. These are expected to provide a “repository of best-practice examples” (Faivre et al., 2017:513) that can be replicated globally. This paper focuses on three Horizon 2020-funded NBS demonstrator projects: Connecting Nature, URBAN GreenUP and Grow Green, each of which brings together a suite of urban partners from both within and outside the European Union (EU). It examines the internal ‘politics’ i.e., the aims and internal governance and implementation issues associated with these projects, and analyses how partners perceive the NBS concept. To engage with these aims, interviews were conducted with a diverse set of NBS ‘practitioners’ working within the three projects. Analysis showed that the projects aim to influence climate-change resilient and sustainable urbanism through the process of retrofitting cities with small-scale green and blue interventions, as well as help the EU secure stronger diplomatic relations with neighbouring non-EU countries and key international trade partners. It also illustrated that for many project partners, NBS is perceived to be a novel concept, because it re-frames pre-existing terms such as Green and Blue Infrastructure (GBI) and Ecosystem Services (ES) in a way that makes principles of urban greening more understandable to lay audiences and more politically palatable for urban governments. However, partners also warn that this framing of NBS has led to a narrow and idealised representation of nature; one that simultaneously undervalues biodiversity and oversells the capacity of natural processes to provide ‘solutions’ to urban climate vulnerability and broader patterns of unsustainable urbanism.